Teologi Persis : Tafsir Ayat-Ayat Pahala Orang Beriman dan Beramal Sholeh dalam Buku Ilmu Tauhid Karya KH. Aceng Zakaria. - Nugraha Insan Nur Akbar; Haris Muslim (Jurnal Syntax Fusion, 2026)
This study departs from the urgent problem of moral decline in contemporary society, which is closely related to the weakening of tawhid education and the lack of understanding and internalization of the rewards promised by Allah in the Qur’an. The purpose of this research is to analyze the composition of the book Ilmu Tauhid by KH. Aceng Zakaria, to examine the interpretation of Qur’anic verses concerning rewards for those who believe and perform righteous deeds in the book, and to explore the characteristics of Persis theology. This research employs a qualitative approach with a library research design. The study focuses on the thoughts of KH. Aceng Zakaria and his works, particularly Ilmu Tauhid and Pokok-Pokok Ilmu Tauhid, as primary sources, supported by Tafsir Ibnu Katsir. Data were collected through documentation techniques and analyzed descriptively to understand the interpretative approach and theological framework used. The findings indicate that Ilmu Tauhid is a compilation of teaching materials originally delivered at Pesantren Ahad. The interpretation of reward verses emphasizes the vastness and comprehensiveness of divine rewards for believers who perform righteous deeds. Furthermore, Persis theology is characterized by a puritan orientation that seeks to purify Islamic teachings from elements of shirk, superstition, and heresy. This study recommends further scholarly exploration of contemporary theological and exegetical products to enrich Qur’anic studies and methodological discourse in Islamic scholarship.